Mirabai and the Ethic of Universal Suffering: Reading Bhajans in Indian Pedagogy. Issue 1 (16th June 2022) - Varghese, Ritu; Rath, Akshaya K.
Abstract: The sixteenth-century bhakti poet-saint Mirabai is a household name in Indian literary and cultural tradition. Mira bhajans were once read as one belonging to the corpus of bhakti literature, but the radical character of her legend and bhajans has availed her a recognition that transgresses boundaries of time, space and culture. M.K. Gandhi is said to have revived Mira during the Indian freedom struggle movement, ascribing to her qualities that fit precisely into what was needed to become an ideal, 'sacred' and all-enduring woman/icon, during the process of which the hybrid-Mira thus constructed requires a critical reading. This note focuses on a popular Mira bhajan, "Hari tum haro jan ki bhir, " with multiple translations, and addresses the dynamic mechanism of such praxis prevalent in Indian pedagogy which is greatly influenced by the (problematic) historical reading of Mira bhajans which continues till date. The note also explores how such (mis)interpretations could influence the socio-political milieu of an age and propel a misrepresented pedagogy of bhakti literature.